Electrophysiology of cross-language interference and facilitation in picture naming. (March 2016) - Roelofs, Ardi; Piai, Vitória; Garrido Rodriguez, Gabriela; Chwilla, Dorothee J.
Abstract: Disagreement exists about how bilingual speakers select words, in particular, whether words in another language compete, or competition is restricted to a target language, or no competition occurs. Evidence that competition occurs but is restricted to a target language comes from response time (RT) effects obtained when speakers name pictures in one language while trying to ignore distractor words in another language. Compared to unrelated distractor words, RT is longer when the picture name and distractor are semantically related, but RT is shorter when the distractor is the translation of the name of the picture in the other language. These effects suggest that distractor words from another language do not compete themselves but activate their counterparts in the target language, thereby yielding the semantic interference and translation facilitation effects. Here, we report an event-related brain potential (ERP) study testing the prediction that priming underlies both of these effects. The RTs showed semantic interference and translation facilitation effects. Moreover, the picture-word stimuli yielded an N400 response, whose amplitude was smaller on semantic and translation trials than on unrelated trials, providing evidence that interference and facilitation priming underlie the RT effects. We present the results of computer simulations showing the utility of a within-language competition account of our findings.